2014
DOI: 10.1590/s0080-623420140000300021
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for falls in hospitalized adult patients: an integrative review

Abstract: Rev Esc Enferm USP2014; 48(3):537-51 www.ee.usp.br/reeusp/ RESUMEN Objetivo: Identificar los factores de riesgo para la ocurrencia de caídas en pacientes adultos hospitalizados. Método: Revisión integradora de la literatura de artículos publicados entre los años 1989 al 2012 en las bases de datos LILACS, SciElO, MEDLINE y Web of Science. Resultados: La muestra final estuvo compuesta por setenta y un artículos. Entre los factores de riesgo de caídas indicados en esta revisión están los relacionados con el pacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 73 publications
4
69
0
8
Order By: Relevance
“…27 Given the importance of adopting safe practices, corrective and proactive measures must be taken, as well as developing strategies that reduce the occurrence of falls and the resulting harm in hospitalized patients. 28 Impact assessment aims to determine the extent, effectiveness and impact of health promotion programs and policies. This includes using appropriate assessments and research methods to support improvement, sustainability and dissemination programs.…”
Section: Discussionmentioning
confidence: 99%
“…27 Given the importance of adopting safe practices, corrective and proactive measures must be taken, as well as developing strategies that reduce the occurrence of falls and the resulting harm in hospitalized patients. 28 Impact assessment aims to determine the extent, effectiveness and impact of health promotion programs and policies. This includes using appropriate assessments and research methods to support improvement, sustainability and dissemination programs.…”
Section: Discussionmentioning
confidence: 99%
“…15 Falls are shown to be a greater etiologic factor at the extremes of age and this is in agreement with most other studies. [16][17][18][19][20] The small rise in the incidence of falls during the festive periods may also be attributed to alcohol intoxication, indiscriminate use of illegal drugs, carelessness and child abuse.…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 99%
“…A literature review on risk factors for falls has found 18 different countries with publications on the subject, besides identifying that the number of publications has been increasing progressively (31) , portraying the concern with knowledge about the issues involving falls, such as risk factors and prevention of the event in the hospital setting. Similarly, the present study also identified an increase in studies published throughout the period from 2006 to 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Issues, such as polypharmacy (≥4 drugs) and drug side effects are important factors that may increase the risk for falls (20,25,(27)(28)(29)31) . Conceptual definition: the patient describes his or her knowledge about the prescribed drugs related to the increased risk for falls, such as: antihypertensives, antiarrhythmics, diuretics, benzodiazepines, sedatives, antidepressants, anticonvulsants, opioid analgesics, muscle relaxants, antihistamines, insulin, oral hypoglycemic agents; due to the presence of side effects, such as hypotension, bradycardia, somnolence, dizziness, reflex changes, visual changes, hypoglycemia, urinary urgency, intestinal urgency.…”
Section: Indicator (182808) When To Ask For Personal Assistancementioning
confidence: 99%